THU0085 Cr6086, a novel ep4 antagonist with immunomodulatory properties, decreases bone loss in the rat collagen-induced arthritis (CIA) model: a microtomography (MICROCT) study. (12th June 2018) - Lanza, M.; Caselli, G.; Ferrari, F.; Grotti, A.; Cavagnoli, R.; Perrella, M.; Daubine, F.; Ayer, V.; Rovati, L.C.
Abstract : Background: CR6086 is a novel PGE2 EP4 receptor antagonist showing favourable immunomodulatory properties, striking DMARD effects in rodents, and an anti-inflammatory activity targeted to immune-mediated diseases and distinct from that of NSAIDs. Besides its role in controlling T cells, PGE2 is implicated in the aggressive bone erosion of rheumatoid arthritis (RA). Objectives: To characterise CR6086 activity on the bone compartment mostly affected by erosion in the CIA model in rats. Methods: 15 male Lewis rats were immunised by intradermal injection with collagen II in CFA. 5 naïve animals were the sham group. 3 days after boost, oedema was assessed and rats assigned to treatment with vehicle or CR6086 (3 or 10 mg/kg qd). Oedema was measured again on days 7 and 14, and hindlimb joints were blindly scored for clinical signs of arthritis (scale 0–4; from normal=0 to maximally inflamed limb with involvement of multiple joints=4). At sacrifice, hindlimb calcaneus underwent high-resolution X-ray microCT (total and cancellous bone), a sensitive method that allows the reduction of experimental animals in compliance with the 3R rule. Parameters were expressed as the mean of left and right paw. Joints were then scored for histological features. Statistics were performed by ANOVA, correlations by Spearman analysis. Results: CR6086 significantly reduced bone loss in CIA rats (table 1), even at the low dose of 3 mg/kg. The effect on cancellous bone plateaued already at 3 mg/kg, confirming the sensitivity of the metabolically more active districts of bone to the action of EP4 antagonists. There was a strict correlation between clinical score and bone parameters (BMD; figure 1 inset), confirming that bone erosion in CIA is closely associated with arthritis severity. Conclusions: CR6086 is an EP4 antagonist in clinical development for RA (NCT03163966 ). Besides its immunomodulatory activity, CR6086 effectively decreases the aggressive bone erosion that characterises both the CIA model and the early phases of human RA. Disclosure of Interest: M. Lanza Employee of: Rottapharm Biotech, G. Caselli Employee of: Rottapharm Biotech, F. Ferrari Employee of: Rottapharm Biotech, A. Grotti Employee of: Rottapharm Biotech, R. Cavagnoli Employee of: Rottapharm Biotech, M. Perrella: None declared, F. Daubine Employee of: Atlantic Bone Screen, V. Ayer Employee of: Rottapharm Biotech, L. Rovati Employee of: Rottapharm Biotech